Optimizing Digital Archive Management to Improve the Quality of Integrated Public Services - Faizah, Nova Auliyatul; Thohir, Muhammad; Salem, Sultan; Mardhiyah (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study examines the implementation of digital archive management to enhance the quality of one-stop integrated services (PTSP) at the Ministry of Religious Affairs Office, Surabaya. This article used a qualitative case study approach; data were collected through interviews, participatory observations, and document analysis. The findings indicate that adopting the SRIKANDI application has streamlined document storage, retrieval, and distribution, improving efficiency. This system reduced service times and operational costs, evidenced by a daily user increase from 100 to 300 for Umrah registration services. However, challenges include employee resistance to new systems, limited training, and infrastructure constraints. To address these, socialization and capacity-building programs have been implemented. This study highlights the importance of digital transformation in public service, offering greater transparency, efficiency, and enhanced user satisfaction. By aligning with global best practices, the research provides insights for policymakers and public service organizations aiming to implement digital archive management, particularly in developing countries. The study concludes that ongoing investment in technology and human resource development is essential to maximize the benefits of digital archiving. Future research should investigate the long-term impacts of digital archive systems on employee performance and user satisfaction. Comparative studies across various governmental offices could identify best practices, particularly in regions with limited technological infrastructure. Additionally, future research could explore strategies to overcome employee resistance to digital systems.